Real-World Outcomes of Nivolumab in Patients With Unresectable Hepatocellular Carcinoma in an Endemic Area of Hepatitis B Virus Infection - Sung, Pil Soo; Jang, Jeong Won; Lee, Jaejun; Lee, Soon Kyu; Lee, Hae Lim; Yang, Hyun; Nam, Hee Chul; Lee, Sung Won; Bae, Si Hyun; Choi, Jong Young; Han, Nam Ik; Yoon, Seung Kew (Frontiers in Oncology, 2020)
Real-world results of nivolumab monotherapy against HCC are lacking in the hepatitis B virus (HBV)-endemic, Asia-Pacific regions. Moreover, heterogeneous responses to immune checkpoint inhibitors have rarely been described in advanced HCC. The aim of this study is to evaluate the efficacy and safety of nivolumab monotherapy in a real-world setting in 33 Korean patients with unresectable HCC. In our cohort, twenty-nine patients (88%) showed HBsAg positivity. At the time of nivolumab initiation, 4 among 33 patients (12%) were classified as Barcelona Clinic Liver Cancer (BCLC)-B stage and 29 (88%) as BCLC-C stage, respectively. Prior sorafenib treatment was given to 31 (94%) patients, and 13 (39%) received prior regorafenib treatment. For the liver reserve, patients were classified as Child–Pugh class A (79%) and B (21%), respectively. Grade 3 toxicities occurred in one patient, who developed pneumonitis after 5 cycles of nivolumab treatment. Best overall responses were complete response in 2 patients out of the 33 enrolled patients (6%), partial response in 4 patients (12%) and stable disease in 4 patients (12%). With 29 patients having images for the response evaluation, the objective response rate was 21.4%. The median overall survival (OS) of the cohort was 26.4 weeks (range 2.3-175.1). Achieving objective responses, pre-treatment small tumours (maximal diameter less than 5 cm) and favourable liver function as assessed by Albumin–Bilirubin grade were significant factors for the favourable OS. Interestingly, differential responses to nivolumab among multiple tumours in a single patient were noted in 6 patients (18%). In these patients, small metastatic tumours were regressed, although their larger tumours did not respond to nivolumab monotherapy. In summary, nivolumab treatment seems clinically efficacious in treating unresectable HCC in an endemic area of HBV infection. Further prospective evaluation is required to overcome the heterogeneous efficacy of nivolumab monotherapy according to the baseline tumour burden.